Natural Resource Management in the Perspective of Fiqh Rules: An Islamic State Budget Proposal For Indonesia - Aang Kunaifi; Achmad Fachruddin Syah (Perhimpunan Intelektual Muslim Indonesia, 2023)
One of the measuring tools to determine the level of progress of a country is the level of consumption per capita of its population. The level of consumption is the main indicator of purchasing power that shows the level of welfare of the population of a country. Increased purchasing power and welfare can be created through various policies, one of which is reducing production costs. One component of production costs that can be eliminated is taxes, so it is necessary to initiate a state revenue budget without taxes. This study aims to calculate the potential of natural resources in Indonesia that can be explored and exploited as the main source of income in the State Revenue and Expenditure Budget. This research uses a literature study approach from reliable sources. Data and documents are processed to be evaluated economically and classified into three categories, namely energy sources or mining products, forest products, and marine products. The budgeting analysis is carried out with a study of muamalah fiqh which will produce a formulation or proposal for the state budget of revenue and expenditure in an Islamic perspective. The findings in this study indicate that the economic value of natural resources produced in Indonesia is capable of generating real wealth that is relevant to be used as the main source of income, in addition to sources of zakat, infaq, waqf, and grants which are also sources of state income in an Islamic perspective. Through this paper, it is hoped that it will create understanding and awareness among state leaders and managers to optimize natural resources in the policy of state revenue sources, so that taxes which are production costs can be minimized or even abolished. Thus the ideals of creating people's welfare can be realized immediately.